How coaches` motivations mediate between basic psychological needs and well-being/ill-being - Alcaraz, S.; Torregrosa, M.; Viladrich, C. (Research Quarterly for Exercise and Sport, 2015)
Purpose: The purpose of the present research was to test how behavioral regulations are mediated between basic psychological needs and psychological well-being and ill-being in a sample of team-sport coaches. Based on self-determination theory, we hypothesized a model where satisfaction and thwarting of the basic psychological needs predicted coaches` behavioral regulations, which in turn led them to experience well-being (i.e., subjective vitality, positive affect) or ill-being (i.e., perceived stress, negative affect). Method: Three-hundred and two coaches participated in the study (Mage = 25.97 years; 82% male). For each instrument employed, the measurement model with the best psychometric properties was selected from a sequence of nested models sustained by previous research, including exploratory structural equation models and confirmatory factor analysis. These measurement models were included in 3 structural equation models to test for mediation: partial mediation, complete mediation, and absence of mediation. Results: The results provided support for the partial mediation model. Coaches` motivation mediated the relationships from both relatedness need satisfaction and basic psychological needs thwarting for coaches` well-being. In contrast, relationships between basic psychological needs satisfaction and thwarting and ill-being were only predicted by direct effects. Conclusion: Our results highlight that 3 conditions seem necessary for coaches to experience psychological well-being in their teams: basic psychological needs satisfaction, especially relatedness; lack of basic psychological needs thwarting; and self-determined motivation.